1998
DOI: 10.1097/00006123-199801000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Report of a National Neurosurgical Emergency Teleconsulting System

Abstract: The system is cost effective and simple to use, has gained widespread physician acceptance, and delivers an image quality superior to that of many commercially available systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…25 Image transfer systems have been initiated across the world for many years specifically to address the need for neurosurgeons to evaluate images before the transfer of patients. 5,11,23,29 The effect of these systems, where available, has proved to be significantly beneficial in terms of mitigating cost of unnecessary transfer. One group in Italy found that only 23% of patients (with a mean GCS score of 11) who had images sent on a teleradiology system required transfer after the initial CT images were sent, and only 5% after follow-up CT. 24 A Level 2 trauma center in Israel found that with the implementation of teleradiology, 40% of patients with TBI were successfully treated at their facility, with only 2 patients requiring delayed transfer to a Level 1 center.…”
Section: Discussionmentioning
confidence: 99%
“…25 Image transfer systems have been initiated across the world for many years specifically to address the need for neurosurgeons to evaluate images before the transfer of patients. 5,11,23,29 The effect of these systems, where available, has proved to be significantly beneficial in terms of mitigating cost of unnecessary transfer. One group in Italy found that only 23% of patients (with a mean GCS score of 11) who had images sent on a teleradiology system required transfer after the initial CT images were sent, and only 5% after follow-up CT. 24 A Level 2 trauma center in Israel found that with the implementation of teleradiology, 40% of patients with TBI were successfully treated at their facility, with only 2 patients requiring delayed transfer to a Level 1 center.…”
Section: Discussionmentioning
confidence: 99%
“…Gray et al 4 evaluated a teleconsultation system based on optical scanning technology and reported transmission failures in 6%. Our system transfers original digital images.…”
Section: Discussionmentioning
confidence: 99%
“…Neurosurgical teleconsultation is among the more common applications of telemedicine. Several studies indicate that teleconsultations between a regional neurosurgical department and referring hospitals improve patient outcome, produce more appropriate patient transfers and are cost-effective [2][3][4][5][6][7][8][9][10][11] . Only a few studies have systematically evaluated response time 9 , influence on patient management 2,5,6,11 and benefits in routine clinical practice 8 .…”
mentioning
confidence: 99%
“…Follow up of head trauma through tele consultations has confirmed its usefulness 30 . Gray's reports [31][32][33] on the national neurosurgical tele radiology system in Ireland, is an example of how tele consultation can considerably extend the reach of a small number of neurosurgeons The system connected six major referring hospitals to the only two neurosurgical departments serving the entire population of 3.5 million people. The system was based on Personal Computer's interconnected by leased data circuits and ISDN lines.…”
Section: The Aragonda Storymentioning
confidence: 99%